RANCANG BANGUN APLIKASI KELOMPOK TANI UMA BERINGIN KECAMATAN ALAS BERBASIS WEB - Herfandi Herfandi; M. Julkarnain; Ahmad Fauzul Kabir (Jurnal Informatika Teknologi dan Sains, 2022)
The Uma Beringin Farmer's Group, Alas Subdistrict, in the process of bookkeeping and information is still manual so it is not effective because there are still frequent mistakes between the management and the warehouse, such as stock of fertilizers, seeds and tools. With the development of technology, web-based applications are able to facilitate data processing to the delivery of information so that it can assist farmer groups in managing and controlling organizational strategies to adjust farmer group empowerment to keep it balanced. Therefore, this study designed a web-based farmer group application. This study resulted in a farmer group application that was built to have admin features that can create, read, update, and delete (CRUD) stock of goods, member data, stock of tools, and news. Meanwhile, farmer members have the feature of viewing stock of goods and submitting online pick-up requests. The development method is waterfall, web-based, the design uses the Unified Modeling Language (UML) approach. Software testing using the black box method with the Test Case Equivalence Partitioning technique gets successful conclusions from various types of tests. it is hoped that this application can help the Uma Beringin Farmer Group to work efficiently which can increase solidarity and food quality for all farmers.